2013
DOI: 10.1016/j.ajog.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique to measure in vivo uterine suspensory ligament stiffness

Abstract: Objective To describe a new computer-controlled research apparatus for measuring in vivo uterine ligament force-displacement behavior and stiffness and to present pilot data in women with and without prolapse. Study Design Seventeen women with varying uterine support underwent testing in the operating room (OR) after anesthetic induction. A tripod-mounted computer-controlled linear servoactuator was used to quantify force-displacement behavior of the cervix and supporting ligaments. The servoactuator applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Results from our physiologic testing suggest that apical ligament stiffness is not the primary factor contributing to uterine support. In a study by Smith et al, in vivo ligament stiffness only explained 19 % of the variation in POP-Q point C [4]. Therefore, when thinking about the etiology of apical support loss, we may presently have a tendency to overestimate the role of apical ligament stiffness and underestimate other important factors, such as ligament length.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from our physiologic testing suggest that apical ligament stiffness is not the primary factor contributing to uterine support. In a study by Smith et al, in vivo ligament stiffness only explained 19 % of the variation in POP-Q point C [4]. Therefore, when thinking about the etiology of apical support loss, we may presently have a tendency to overestimate the role of apical ligament stiffness and underestimate other important factors, such as ligament length.…”
Section: Discussionmentioning
confidence: 99%
“…The technique for making measurements of cervix location in the OR using a computer-controlled servoactuator device has been previously described [4] and is shown in Fig. 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While ex vivo studies have provided very valuable information with regards to the elastic and viscoelastic properties of the USL, in vivo mechanical tests of the USL, whenever possible, are ideal. 36,43 However, these tests can be conducted in humans only over a very short period of time due to ethical concerns associated with subjecting patients to mechanical testing for extended periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…The constitutive model was evaluated in Abaqus and the evaluation result showed that it was stable. The material properties values for the apical supports and uterine support tissues, which include a cardinal ligament (CL) and uterosacral ligament (USL) on each side of the vagina, were taken from our recent in vivo tissue tests (Luo et al, 2014b; Smith et al, 2013) on healthy women. In those studies we used a computer-controlled linear servo actuator to apply a continuous force and simultaneously recorded cervical displacement.…”
Section: Methodsmentioning
confidence: 99%